A SNAPSHOT OF STUDENTS’ ABILITY IN WRITING SHORT ESSAYS AND THEIR TRANSLATION OF ISLAMIC EDUCATION PROGRAM - Elvina Gusman; Nurul Indah (Journal of English Education and Linguistics, 2020)
This research was aimed to see how is students’ ability in writing short essays and their translations majoring in Islamic Education Program, STAIN Mandailing Natal. Generally, the components of writing are vocabulary, sentence structure, mechanic, content and organization. This research concerns about how to write short essays and their translation correctly. Descriptive method is used in this research. In collecting the data, the author used students’ test results of Islamic Education Program. Then, the data is analyzed by using the qualitative method. The results of this study indicate that from 20 students majoring in Islamic Education Program, 3 students were able to write short essays appropriately, while 10 students were only able to write a few sentences, and 7 students were able to write one sentence. Three students’ short essays applied writing components very well. 10 were already using writing components well. 7 short essays were categorized as lacking and no writing components. Related to their translation, 3 short essays were easy to understand. 10 short essays were mediate, and 7 short essays were poor.